2018
DOI: 10.1037/abn0000372
|View full text |Cite
|
Sign up to set email alerts
|

Eye avoidance in young children with autism spectrum disorder is modulated by emotional facial expressions.

Abstract: Individuals with autism spectrum disorder (ASD) exhibit a reduced duration of eye contact compared with typically developing (TD) individuals. This reduced eye contact has been theorized to be a strategy to relieve discomfort elicited by direct eye contact (Tanaka & Sung, 2016). Looking at threatening facial expressions may elicit more discomfort and consequently more eye avoidance in ASD individuals than looking at nonthreatening expressions. We explored whether eye avoidance in children with ASD is modulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 58 publications
2
22
0
Order By: Relevance
“…A further subtle but significant finding showed that when an accidental event happened to a puppet in the interlocutor’s hand, ASD participants took significantly longer to begin to monitor the face of the interlocutor compared to both TD and SLI participants (see Figure 6). These findings are indicative of an ASD-specific difference in the allocation of social attention, and this is consistent with previous studies [98,111,128,131]. Delays in looking to the interlocutor’s face indicate that participants with ASD, unlike TD counterparts, did not immediately use the interlocutors face as a social reference marker to indicate detection of the ‘accident’.…”
Section: Face-to-face Interaction Paradigmssupporting
confidence: 90%
See 1 more Smart Citation
“…A further subtle but significant finding showed that when an accidental event happened to a puppet in the interlocutor’s hand, ASD participants took significantly longer to begin to monitor the face of the interlocutor compared to both TD and SLI participants (see Figure 6). These findings are indicative of an ASD-specific difference in the allocation of social attention, and this is consistent with previous studies [98,111,128,131]. Delays in looking to the interlocutor’s face indicate that participants with ASD, unlike TD counterparts, did not immediately use the interlocutors face as a social reference marker to indicate detection of the ‘accident’.…”
Section: Face-to-face Interaction Paradigmssupporting
confidence: 90%
“…One explanation for this atypicality could be that neutral faces are perceived as more ambiguous in social information for the ASD group, and hence, shifting fixation away from the eyes of neutral faces may be adopted by autistic individuals as a compensatory strategy to alleviate any potential threatening feeling associated with neutral faces. However, a very recent study from Wang, Lu, Zhang, Fang, Zou and Yi [128] found evidence of eye avoidance exclusively for angry faces in ASD children compared to TD controls. There have also been other inconsistent reports for eye avoidance.…”
Section: Face- and Emotion-processing Paradigmsmentioning
confidence: 99%
“…As an extension to this, the current study itself directly reveals a visual disengagement difficulty for central angry faces at the endogenous attention level in children with ASD. Furthermore, considering that angry faces convey obvious threatening information, this delay could reflect hypervigilance for threats when they are presented centrally in this group [ 45 ], and this hypervigilance could result in less flexible attentional disengagement from this type of stimuli in ASD children.…”
Section: Discussionmentioning
confidence: 99%
“…To examine how the eye‐looking time changed over time, we proposed a novel data‐driven method based on a moving‐average approach (Dankner, Shalev, Carrasco, & Yuvalgreenberg, ; Wang, Hu, et al, ; Wang, Lu, et al, ) with a cluster‐based permutation test to control the family‐wise error rate (Maris & Oostenveld, ). Specifically, we segmented each set of trial data (600 sample data in total) into epochs of 250 ms (30 sample data), with 29 sample data overlap, resulting in 571 epochs for each trial.…”
Section: Methodsmentioning
confidence: 99%